Education of the minority communities in Vietnam : a case study of Quanson Mountainous District, Thanhhoa Province - Pham Anh Tuan; Ahmad, Mokbul M.; Routray, Jayant Kumar; Soparth Pongquan; Ford international fellowships program (US) (Pathum Thani : Asian Institute of Technology, 2013)
The research examined two high schools (Grade 10 - 12) in a mountainous district where a minority ethnic community are living. This study found reasons for low enrolment and high drop - out among the children and analyze high schools{u201F} quality about: Teachers, curriculum and students. The research was conducted in four ethnic minority schools. Data were collected from both primary and secondary sources. The primary data contained by a questionnaire survey of 71 students in 28 classes, 24 teachers, 32 parents a nd students and some in - depth interviews with key informants, also group discussion. The main results of this study displayed two high schools in Quanson are lacked physical facilities, low income of teachers, poverty of students{u201F} families, underage marria ge, social problems to schools and low awareness about education of local people etc. The quality of teachers and curricula are not high and most of all ethnic minority students are low. The parents usually need more labor in family works and also childre n prefer to earn money than studying. The main findings of research would point out some policies and recommendations to improve the quality of education in the study area. There is a need for training, rising quality of teacher, changing teaching method, curriculum and support finance for teachers and poverty student{u201F}s families.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Regional and Rural development Planning
Thesis (M. Sc.) - Asian Institute of Technology, 2013
Keywords: Education -- Vietnam -- Thanhhoa